Approximately symmetric electrowetting on an oil-lubricated surface. Issue 34 (27th May 2020) - Yuan, Xi; Tang, Biao; Barman, Jitesh; Groenewold, Jan; Zhou, Guofu
Abstract : An attractive oil-lubricated electrowetting (EW) material system which could suppress the charge trapping on the dielectric/water interface and improve consequently asymmetric EW was proved. Abstract : As the most widely used insulator materials in the electrowetting (EW) systems, amorphous fluoropolymers (AFs) provide excellent hydrophobicity, dielectric properties and chemical inertness; however, they suffer from charge trapping during electrowetting with water and the consequent asymmetric phenomenon. In this study, an ultra-thin oil-lubricated AF surface was proposed to release the charge trapping in the dielectric layer and further suppress the polarity-dependent asymmetry during electrowetting. The negative spontaneously trapped charges gathering on the dielectric/water interface with aging time were characterized by various measurements and calculations, which explained the polarity dependence of the asymmetric electrowetting. Approximately symmetric EW curves withstanding water aging were obtained for the oil-lubricated AF surface, confirming the blocking effect on charge trapping induced by the lubricated surface. The improved reversibility of EW with low contact angle hysteresis brought by the oil-lubricated surface was also demonstrated. This study reveals the mechanism behind the asymmetric EW phenomenon and offers an attractive oil-lubricated EW material system for suppressing the charge trapping on the dielectric/water interface, which can significantly improve the manipulation of the EW devices.